R. A. REISS: NEUTRALITY IS NOT POSSIBLE IN THE FACE OF CRIME - Jakovljević, Nevena (Serbian political thought, 2025)
The work of Dr. Uroš Šuvaković, a distinguished professor at the Faculty of Teacher Education, University of Belgrade, R. A. Reiss: Neutrality is not possible in the face of crime, is a very interesting read that encourages the reader to ask themselves about the sociological and historical aspects of Serbian tradition and culture, which, as the author himself states, we tend to forget. And that is precisely why the idea of ​​publishing this book on the occasion of the 110th anniversary of the arrival of Rudolph Archibald Reiss (Rudolph Archibald Reiss, 1875–1929) in the Kingdom of Serbia and, at the same time, the 95th anniversary of the death of this great Serbian friend, is a reflection of the author's aspiration that what Reiss did for the Serbian people then, during and after the First World War, should not be forgotten. The author himself treats this book as a personal contribution to the "culture of memory" of Serbs, in the specific case of remembering the works of Archibald Rice.
Keywords: /